TECHNOLOGICAL DEVELOPMENT OF A PROCESS FOR IMPROVING DIGESTION OF DAIRY PRODUCTS BY ß-GALACTOSIDASE DASA IMMOBILIZED - Woolkott Hurtado, J. (1998)
Five strains of Kluyveromyces marxianus a one of Gandida pseudotropicalis were cultured in medium M-1 for productión of 13- galactosidasa (E.C : 3:2:1:23). The strain Kluyveromyces mandanus NRRL- Y - 1109 was selecteed for the best production of enzyme and the maxímum yield of enzyme was obtaíned on 5% of lactose supplemented with 0.5% yeast extract , 0.75% (NH4)2 S04 y 0.45% K2HP04 (w/v). lt obtained a yield of 5.43 U/mg of protein and 1.31 A.UoNPcl mg of dry weight. The extraction of the enzyme from viable cells was performed by toluene 2% (v/v), during 15 hours of treatment at 30°C, in 0.1 M potassium phosphate buffer, pH 7.0 ± 0.1, supplemented with 1 mM magnesium and 0.1 mM manganese sulfate . The yield of immobilization of enzyme on chitin treated with glutaraldehide was 41%, being the optimum pH of 6.6 ± 0.1. The values of Km and Vm for immobilized using lactase as substrate were 49 mM y 161 micromole/m im/ g of support respectivelity. The Ki by galactose was 44 mM. The half-life of immobilized enzyme at 40 ºe was 176 min, maintaining 99% of activity for 3 months at 4°C and retained 64 % of original activity even after being used for 20 times.